MANAGEMENT OF AL-MUHTADIN TOLOTIO ELEMENTARY SCHOOL, BONEPANTAI DISTRICT, BONE BOLANGO REGENCY - Isa Pakaya, Cindriyani; Van Gobel, Lisda; Djaba, Misbahudin (Yayasan Nuraini Ibrahim Mandiri, 2025)
This study aims to describe the management of Madrasah Ibtidaiyah (MI) Al-Muhtadin in Tolotio Village, Bonepantai District, Bone Bolango Regency, including planning, organization, implementation, and evaluation within the context of a rural Islamic school. The research method used was descriptive qualitative, with data collection techniques including in-depth interviews, participant observation, and document analysis. The results indicate that planning is participatory and based on local needs; organization is characterized by a flexible and collaborative division of tasks; implementation of academic and religious programs is adaptive to school conditions; and evaluation and supervision prioritize a reflective approach and moral strengthening. The conclusion of this study is that despite limited resources, MI Al-Muhtadin is able to provide quality and relevant education through collaborative leadership and strong support from the surrounding community. Keywords: Madrasah Management, Islamic Education, Rural Schools, Community Participation